Peningkatan Kemampuan Berbicara di Depan Umum Melalui Pelatihan Public speaking pada SMA Pasundan 1 Kota Bandung - Almadina Rakhmaniar; Rasman Sonjaya; Muhammad Deni; Retno Ayu Sagita Damayanti (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to improve the public speaking skills of Pasundan 1 High School students in Bandung City through public speaking training. The problems faced by students are a lack of understanding and awareness of the importance of public speaking skills, limited opportunities and platforms to apply these skills in the school environment, as well as a more theoretical teaching approach. The solution offered is to hold public speaking seminars and workshops with an interactive and practical approach, as well as encouraging the development of extracurricular programs that focus on improving public speaking skills. This training was carried out in three stages: preparation, implementation, and monitoring and evaluation. The results of the activities showed an increase in students' self-confidence, a reduction in anxiety about speaking in public, as well as an increase in communication skills and critical thinking abilities. This research makes a significant contribution to improving students' public speaking skills, which is vital for their future personal and professional development.